The Influence of Convenience, Design, Trustworthiness, Price, And Various Food Choices On Customer Loyalty Through Perceived Value Among Gofood Customers In Surabaya - Kelvin Andreas Theli; Yolanda Soedibyo (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
PT. Gojek Indonesia, a technology company founded by Nadiem Makarim in 2009 in Jakarta, has developed into one of the leading digital platforms in Indonesia, operating in 167 cities and districts. GoFood is a well-known and frequently used e-commerce platform in Indonesia. GoFood functions as an online food or drink delivery service, so that users can order food or drinks without having to go to the restaurant's physical location, making the process more practical and time efficient. This research aims to determine the influence of Convenience, Design, Trustworthiness, Price, Various Food Choices, on Customer Loyalty through Perceived Value. This research is causal in nature using a quantitative approach and processing using AMOS 24.0 software and have 175 GoFood customers in Surabaya which have been collected using the Snowball Sampling sampling technique. The results of this research are that all variables have a positive and significant effect on Customer Loyalty, which are Perceived Value, Convenience, Design, Trustworthiness, Price, Various Food Choices.